2017
DOI: 10.3892/ol.2017.6429
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-708 functions as a tumour suppressor in hepatocellular carcinoma by targeting SMAD3

Abstract: Abstract. Hepatocellular carcinoma (HCC) is the most frequent subtype of primary liver cancer and the third most common cause of cancer-associated mortality worldwide. Previous studies have reported that microRNAs (miRNAs) serve key roles in the carcinogenesis and progression of HCC by regulating gene expression. The present study investigated the expression patterns, biological roles and underlying mechanisms of miRNA-708 (miR-708) in HCC. The expression levels of miR-708 in HCC tissue samples and cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The suppressive role of this signalling in cancers reflects in inhibition on tumour formation and inducement of growth arrest and apoptosis . On the other hand, TGF‐β/SMAD signalling shows the activity to promote tumour progression and metastasis, by inducing angiogenesis, inflammation and EMT . Yoshida and the colleagues have concluded, based on the reviews of the publications, that TGF‐β acts as a growth suppressor in normal epithelial cells after transient Ras activation.…”
Section: Discussionmentioning
confidence: 99%
“…The suppressive role of this signalling in cancers reflects in inhibition on tumour formation and inducement of growth arrest and apoptosis . On the other hand, TGF‐β/SMAD signalling shows the activity to promote tumour progression and metastasis, by inducing angiogenesis, inflammation and EMT . Yoshida and the colleagues have concluded, based on the reviews of the publications, that TGF‐β acts as a growth suppressor in normal epithelial cells after transient Ras activation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the recovery of Smad3 signaling can restore the chemosensitivity of HCC cells [ 138 ]. Recently, several kinds of microRNAs (miRNA) have been reported to regulate Smad/EMT signaling; in contrast, miRNA-125b and miRNA-708 suppress Smad2 and Smad3 pathway and attenuate EMT [ 139 , 140 ], miRNA-520g down-regulates Smad7 and promotes EMT in HCC cells [ 141 ]. These data suggest that TGF-β/Smad-induced EMT signaling have important roles in the generation of highly invasive and chemoresistant cells with stem cell-like features in HCC.…”
Section: Emt In Liver Fibrosis and Hcc Progressionmentioning
confidence: 99%
“…Over the past few decades, mounting studies have suggested that miRNAs can act as oncogenes or tumor suppressors in most types of cancer, including breast cancer [7], gastric cancer [8], prostate cancer [9] and colorectal cancer [10]. With regard to HCC, multiple previous studies have also demonstrated that miRNAs are involved in HCC progression [1113]. However, only few reports regarding the roles of miRNAs in HBV-related HCC.…”
Section: Introductionmentioning
confidence: 99%